Kinetic and Stoichiometric Evaluation of Free Radicals Scavengers Activities Based on Diphenyl-Picryl Hydrazyyl (Dpph) Consumption - Lissi-Gervaso, E; Campos-Deramond, A; Campos-Deramond, A (Sociedad Chilena de Quimica, 2012)
Kinetics and stoichiometric measurements based on the reactions of stable free radicals are among the most employed procedures in the evaluation of antioxidant activities of pure compounds and complex mixtures. In the present work it is shown that initial rates of diphenyl-picryl hydrazyl (DPPH) consumption elicited by cinnamic acid derivatives are closely related to their reactivity towards peroxyl radicals. This implies that kinetic data regarding DPPH bleaching can be useful on the evaluation of antioxidant reactivities. On the other hand, data obtained at a single (long) reaction time are unrelated to the reactivity of the antioxidants and mostly reflect the number of phenol groups present in the tested sample.